Infestation of weed species in pre-planting of soybean in succession to winter crops - Concenço,G. (2013)
This study aimed to evaluate different crops and plant species planted after soybeans for one year, in terms of their potential to inhibit the occurrence of weed species. The following crops that were planted as second crop after soybeans were evaluated: (1) corn (Zea mays) planted at spacing of 90 cm between rows, intercropped with Brachiaria ruziziensis in the inter-rows; (2) sunflower (Helianthus annuus); (3) crambe (Crambe abyssinica); (4) radish (Raphanus sativus); (5) rapeseed (Brassica napus); and (6) winter fallow - no plantation after soybeans. Phytosociological characterization of weed species was carried out at the pre-planting of soybeans in the following cropping season. Estimations of relative abundance, relative frequence, relative dominance and Importance Value Index were made for each species present. Areas were also intra-characterized by the diversity coefficients of Simpson and modified Shannon-Weiner, and areas were compared using the Jaccard similarity coefficient for presence-only, by multivariate cluster analysis. In the short‑term (a single cropping season), cultivation of winter crops do contribute for lower occurrence of weed species at the pre-planting of soybeans on the subsequent cropping season. The suppressive effects depend both on the species grown in the winter and in the amount of straw left on the soil by these winter crops. Radish was more efficient in inhibiting the occurrence of weed species and rapeseed showed composition of infestation similar to that observed at the area under fallow.